Критерії повноцінності та безпечності трансплантата стовбурових клітин пуповинної крові людини - Салютін, Р. В.; Лобинцева, Г. С.; Зубкова, Г. А.; Дроздович, І. І.; Паляниця, С. С.; Давидова, Т. І. (Clinical Endocrinology and Endocrine Surgery, 2011)
The results of the definition of criteria of quality of stem cells from umbilical blood to ensure their adequacy and safety in transplantation.It is shown that umbilical cord blood as a source of stem cells has several advantages compared with bone marrow and peripheral blood, though it contains fewer stem cells.Developing criteria for quality and adequacy of stem cells will improve the efficiency of their transplants as a treatment modality.